Heterogeneous plaque geometry is associated with major adverse cardiovascular events. (3rd October 2022) - Gu, Z S; Huang, Y; Costopoulos, C; Jessney, B; Bourantas, C; Teng, Z; Maehara, A; Raber, L; Stone, G; Bennett, M R
Abstract: Objectives: To determine whether coronary artery plaque-lumen geometry predicts major adverse cardiovascular events (MACE), and incorporating geometric measures enhances risk stratification from intravascular imaging. Background: Prospective studies show that only a minority of plaques with higher-risk features result in future MACE, indicating the need for more predictive markers of plaque vulnerability. Plaques show heterogeneous structures and plaque-lumen geometry, both of which can promote high plaque structural stress (PSS); however, the relationships between geometric heterogeneity and MACE or PSS are unknown. Methods: We examined plaque-lumen curvature, irregularity, lumen aspect ratio (LAR), roughness, PSS and their longitudinal heterogeneity (Figure 1A) in 35 non-culprit lesions (NCL) associated with MACE and 66 propensity-matched no-MACE NCL from the PROSPECT (Providing Regional Observations to Study Predictors of Events in the Coronary Tree) study. Causes of heterogeneous geometry and PSS were examined using a separate group of co-registered virtual histology-intravascular ultrasound (VH-IVUS) and optical coherence tomography (OCT) images (n=53 plaques). Results: Plaque geometry heterogeneity indices (HI) were increased in NCL MACE vs. no-MACE lesions across the whole plaque and peri-minimal luminal area (MLA) segments (HI curvature: p=0.002; HI irregularity: p<0.001; HI LAR: p=0.001; HI roughness: p=0.002). Peri-MLA HI roughness was an independent predictor of future MACE (hazard ratio: 3.69, p<0.001) (Figure 1B). Inclusion of HI roughness improved identification of NCLs leading to MACE in VH-defined thin-cap fibroatheromas (VH-TCFA, p=0.005), MLA ≤4mm 2 (p=0.001), and plaque burden (PB) ≥70% (p<0.001) (Figure 1C–E), and further improved the ability of PSS to identify MACE NCLs in VH-TCFA (p=0.041), MLA ≤4mm 2 (p=0.033), and PB ≥70% (p<0.001). HI roughness generally corresponded with HI PSS, but was also increased at sites of local calcification and multilayering. Conclusions: Plaque-lumen geometric heterogeneity is increased across whole plaque and peri-MLA segments of NCLs causing MACE. Inclusion of geometric heterogeneity may improve the ability of intravascular imaging to predict MACE. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): British Heart Foundation